(untitled) (Annals of Medical Research, 2021)
Aim: Kidney biopsy is the golden standard method for both diagnosis and determining the therapeutic options in renal parenchymal diseases. In our study, we aimed to evaluate the results of kidney biopsies that have been performed in the last 6 years.Material and Methods: The results of 202 patients who underwent renal biopsy in our hospital between 2011 and 2017 were retrospectively evaluated.Results: The mean age of the patients were found as 50.7 ± 15.1 years. The male and female numbers of the patients were 114 (56.4%) and 88 (44.6%) respectively. Proteinuria in 96 patients (47.5%) was the most common indication for kidney biopsy. When we evaluated the biopsy results; 123 (60.9%) of the patients were diagnosed for primary glomerulonephritis, 43 (21.3%) of the patients were diagnosed for secondary glomerulonephritis while 36 (17.8%) of the patients were diagnosed for tubulointerstitial involvement. The most common pathological diagnosis were Focal Segmental Glomerulosclerosis in 40 patients (19.8%) and Immune Globulin A Nephropathy in 38 patients (18.8%) in our patient group who had primary glomerulonephritis.Conclusion: The most common pathology of the patients who had native kidney biopsy was primary glomerulonephritis. 61.3% of the patients who had diagnosis for Diabetes Mellitus had pathologies other than Diabetic Nephropathy shows the importance of screening any other co-existing pathologies in this group of patients. Uncontrolled use of the drugs accelerates the rate of Tubulointerstitial Nephritis as the primary and co-existing pathological diagnosis.Keywords: Renal Pathology; Primary; Secondary; Tubulointerstitial; Co-Existing.